lemme use a slightly different equation, just the variables differ, but is basically the same you have there.
A)
![\bf \textit{Amount of Population Growth, \boxed{\textit{10th day}}} \\\\ A=Pe^(rt)\qquad \begin{cases} A=\textit{accumulated amount}\dotfill&5287\\ P=\textit{initial amount}\dotfill &P\\ r=rate\to r\%\to (r)/(100)\\ t=\textit{elapsed time}\dotfill &10\\ \end{cases} \\\\\\ A=5287e^(10r) \\\\[-0.35em] ~\dotfill](https://img.qammunity.org/2020/formulas/mathematics/college/bcbokrfnsw45zjz2nf80kbcj0kwym0fzty.png)
![\bf \textit{Amount of Population Growth, \boxed{\textit{21st day}}} \\\\ A=Pe^(rt)\qquad \begin{cases} A=\textit{accumulated amount}\dotfill&692\\ P=\textit{initial amount}\dotfill &P\\ r=rate\to r\%\to (r)/(100)\\ t=\textit{elapsed time}\dotfill &21\\ \end{cases} \\\\\\ 692=Pe^(21r) \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ \begin{cases} 5287=Pe^(10r)\\ 692=Pe^(21r) \end{cases}](https://img.qammunity.org/2020/formulas/mathematics/college/kc354f4dngq0j4m04dp20bjfebihmb1c4j.png)
![\bf \cfrac{5287}{e^(10r)}=P\qquad therefore\qquad \stackrel{\textit{doing some substitution}}{692=Pe^(21r)\implies 692=\left( \cfrac{5287}{e^(10r)} \right) e^(21r)} \\\\\\ \cfrac{692}{5287}=\cfrac{e^(21r)}{e^(10r)}\implies \cfrac{692}{5287}=e^(21r)e^(-10r)\implies \cfrac{692}{5287}=e^(11r)](https://img.qammunity.org/2020/formulas/mathematics/college/ndyqzdyz3l7w1mrvjo73w1dwgvfeolricc.png)
![\bf ln\left( \cfrac{692}{5287}\right)=ln\left( e^(11r) \right)\implies ln\left( \cfrac{692}{5287}\right)=11r\implies \cfrac{ln\left( (692)/(5287)\right)}{11}=r \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ ~\hfill -0.18486\approx r~\hfill](https://img.qammunity.org/2020/formulas/mathematics/college/fom8apmsn12jmwdcy6jced8qqqz66u6wdd.png)
B)
![\bf 5287=Pe^(10r)\implies 5287=Pe^(10(-0.18486))\implies 5287=Pe^(-18.486) \\\\\\ \cfrac{5287}{e^(-18.486)}=P\implies 6360.53\approx P](https://img.qammunity.org/2020/formulas/mathematics/college/s5zfmpjh9ctuf8xvga74wzec0sd9322v86.png)
and we can round that up to a whole leaf of 6361, or truncate it to 6360, chances are is the latter.
C)
![\bf \stackrel{\textit{only 1 leaf}}{1}=(6360.53)e^(-0.18486t)\implies \cfrac{1}{6360.53}=e^(-0.18486t)\ \\\\\\ ln\left( \cfrac{1}{6360.53} \right)=ln\left( e^(-0.18486t) \right)\implies ln\left( \cfrac{1}{6360.53} \right)=-0.18486t \\\\\\ \cfrac{ln\left( (1)/(6360.53) \right)}{-0.18486}=t\implies 47.38\approx t](https://img.qammunity.org/2020/formulas/mathematics/college/klrsfrbp4aziqjgij6b35o7jal5s2685pd.png)
and we can round that up to 47 days even.